Using automated in-paddock weighing to evaluate the impact of intervals between liveweight measures on growth rate calculations in grazing beef cattle - Imaz, José Augusto; García, S.C.; González, Luciano A. (Elsevier, 2020)
Animal liveweight (LW) data collection is key to monitor health, nutrition, and reproduction of cattle. However, this is challenging in grazing systems using traditional technology due to the need of mustering animals into handling facilities with the required frequency. Such practical constraints make it difficult to gather frequent LW data to study the effects of different intervals between LW measures (ILW) to accurately describe the growth pattern of animals. However, nowadays, frequent LW data can be acquired remotely using in-paddock technologies without the need to handle the animals. Thus, the aim of this study was to quantify the impacts of ILW to capture LW and growth patterns of three beef cattle categories (calves, weaners, and cows). Liveweight data were collected using in-paddock walk-over-weighing scales (WOW), placed before the access to the water trough. The lengths of continuous LW data records were 112, 224 and 1460 days (4 years) for calves, weaners and mature cows, respectively. These datasets were then subsampled to simulate different ILW with one LW record every: (a) 1, 2, 4, 8 and 16 weeks for calves; (b) 1, 2, 4, 8, 16 and 32 weeks for weaners; and (c) 1, 2, 4, 8, 16, 26, 32, 52 (1 year) and 208 weeks (4 years) for cows. Daily LW change (LWC) was calculated as the difference between two consecutive LW observations divided by the number of days elapsed. The minimum (Min), mean, maximum (Max), standard deviation (STD) and coefficient of variation (CV) for LW and LWC were calculated for each animal and ILW. Minimum and Max LWC, and STD and CV of LW were affected (P < 0.05) by ILW in all animal categories whereas no effects (P > 0.05) were observed for the rest of the variables. The relationship between ILW and LW variability (STD, CV) was quadratic for calves and weaners but linear for cows (P < 0.05). In comparison to daily data, the minimum frequency required to capture Min and Max LWC was 2 weeks for calves and weaners, and 8 weeks for cows. In addition, an ILW of 4 (calves and weaners) and 8 (cows) weeks was needed to achieve similar STD and CV of LW and LWC compared to daily ILW. These results, obtained in grazing conditions, suggest that WOW could be used more strategically within and between farms, as LW data need to be captured at regular intervals but not necessarily daily.